Effects of Climatic Variations and Changing Land Use/Land Cover on Flooding in Southern Nigeria - Nwachi Christy Chidiebere; Ogbonna Chukwuemeka Godswill; Ekwe Chidumebi Anthony; Umegboro Johnbosco Ikechukwu (Indonesian Journal of Environmental Management and Sustainability, 2024)
The prevalence of flooding in Nigeria in the past few years (with its devastating consequences) has become a source of concern for policymakers and researchers alike. Scholars have attributed the high frequency of flooding, particularly in the southern region of Nigeria, to several factors; climatic variation and land use/land cover changes are themes that fall under the domain of natural and anthropogenic causes of flooding, respectively. This study examined climatic variations and changing land use/land cover in southern Nigeria with the view of determining their synergistic effects on flooding. We adopted a mixed approach for data collection with the use of Geographic Information System (GIS), retrieval of primary data from meteorological stations in the region, and field surveys. Findings show a significant decrease in rural land uses like arable lands, wetlands, and undisturbed forests; while there was a corresponding increase in urban/peri-urban land uses like settlements and tree-crop plantations over the period from 1999 to 2019. The land use/land cover changes have manifested in the destabilization of the microclimate, distortion of the carbon circle, loss of biodiversity, reduction of ecosystem services of the natural areas, and flooding. The decadal rainfall trends over the past three decades show consistent extremities with mean rainfall duration decreasing while the mean intensity increases; aggravating soil erosion, urban runoff challenges, and flooding. Climatic variations (mainly extreme rainfall patterns) synergize with inefficient land use management to exacerbate flooding in southern Nigeria. While policymakers in this region may not have the standalone capacity to significantly control climate change and the consequential variations in the local microclimate, they can re engineer land use policies to eliminate or substantially degrade anthropogenic factors that exacerbate flooding.